(untitled) (Heritage, 2024)
Bohumil Para (1861–1915) was an Austro-Hungarian consul who spent most of his diplomatic service in the Ottoman Empire, primarily in the Kosovo Vilayet. He was first employed in Pljevlja, in the Command of the occupation troops (1891–1898), and then in the Consulate in Skopje (1898–1906). Long-term presence in these areas and dedication to work made him a good connoisseur of the situation, so his reports are indispensable material in the reconstruction of the past. Apart from dedication to work, Para was characterized by loyalty and exceptional attachment to the Austro-Hungarian state, which was reflected, among other things, in the translation of his name into German.Due to these facts, his reports should be approached with a degree of caution, and subjectivity can be observed through detailed analysis and comparison with other correspondence. It should be noted that Para served as a consul in Skopje, which, before the opening of the consulate in Mitrovica, was extremely important for Austria-Hungary’s further plans and penetration to the east. The analyzed report is dated August 6, 1901 and was created after the events in Mitrovica and Novi Pazar, known in historiography as the Kolašin Affair. In Para’s report, which is quite voluminous, very little attention is paid to specific events on the ground. His attention is more aroused by the presence of the Russian consul Mashkov and the companions of Captain Ritich and Vsevolod Sviatkovsky, a correspondent of the Novoe vremja newspaper. He accuses Captain Ritich of getting familiar with the terrain, i.e. "military-geographical" recordings, while the well-known journalist Sviatkovski is held responsible for the campaign that was conducted in the press of Serbia and Russia against Austria-Hungary and him personally as the instigator of the weapons investigation among the Serbs.Regarding Consul Maskov, Para says that he did not miss the opportunity to agitate among the Christian population against Austria-Hungary and the construction of the so-called Bosnian Railways. In addition to following the activities of Russian diplomacy, Bohumil Para in the report dealt with the personal relationships of certain officials of the Ottoman Empire, looking for those susceptible to Serbian influence. Attention should also be drawn to the vocabulary used by Para in the report. It is a standard terminology found in his reports, as well as in the reports of other Austro-Hungarian consuls. He consistently used the term Christians in different variations to denote the non-Muslim population in the Kosovo Vilayet, although he was well aware that they were Serbs, especially in the area north of the Šara Mountain.In this way, we would say, the Austro-Hungarian propaganda tried to create a new entity. Para used the terms Serbia and Serbian to denote the Kingdom of Serbia and its institutions. The Serbs in the Ottoman Empire are mentioned only as part of the South Slavs, opposed to the Bulgarians around Macedonia. Also interesting is the use of the name of the Albanian leader Isa, whose surname Boljetinac is used in the Serbian / Slavic variant, and not Albanianized, as historians claim today. That variant of the (sur)name, then generally accepted, indicates that it is a newcomer to the Serbian living space. Even a partial review of this report by Para indicates that it is a rather subjective approach, with a clearly prescribed terminological use. This indicates that the Austro-Hungarian diplomacy worked according to precisely established rules, in order to achieve the set tasks.